Seeking Allah, finding Jesus : a former muslim shares the evidence that led him from Islam to Christianity : study guide : eight sessions /: a former muslim shares the evidence that led him from Islam to Christianity : study guide : eight sessions. ([2016]) - Qureshi, Nabeel; Harney, Sherry, 1960-; Harney, Kevin
No abstract available